Type III interferon, age and IFNL gene single nucleotide polymorphisms determine the characteristics of H1N1 influenza infection - Zhu, Wenbo; Wang, Shao; Guan, Chenchen; Liu, Shuangquan; Zhang, Hongbo (Frontiers in Immunology, 2025)
BackgroundHost factors, such as innate immune response, genetic polymorphisms, age, and body weight are important determinants of susceptibility, severity, and responsiveness to treatment of influenza disease. However, the molecular mechanisms underlying these clinical associations remain poorly characterized, particularly regarding IFN-λ-mediated antiviral responses.MethodsWild-type mice and IL-28B-/- mice were used to systematically investigate the antiviral and anti-inflammatory functions of IL-29 or IL-28, respectively. Plaque assay and DNA genotyping were conducted to determine the correlations between IFN-λ polymorphisms and H1N1 infection outcomes. ELISA, Real-time PCR and luciferase reporter assays were carried out to explore the mechanism.ResultsIFN-λ plays an important antiviral and immunoprotective role in H1N1 infection. Specifically, IL-29 and IL-28 exhibit important dual antiviral and anti-inflammaroty roles. Age factor also affects H1N1 clearance and therapeutic responsiveness. Human alveolar epithelial cells (AECs) from young donors support higher H1N1 replication and weak response to antiviral treatment with IL-29. Rs12979860 (IL-28 C/T), rs8099917 (IL-28 T/G) and rs30461 (IL-29 A/G), the three identified single nucleotide polymorphisms (SNPs) in IFNL genes, are also associated with H1N1 outcomes. AECs from rs12979860TT and rs8099917GG donors exhibit higher H1N1 replication and nonresponsiveness to IL-29 antiviral therapy. AECs from rs12979860 TT donors also produce lower levels of IFN and exhibit inhibited promoter activity of IL-29 in response to H1N1 infection. In addition, increased allele frequencies of rs12979860 T and rs8099917 G were associated with higher BMI, another important factor influencing H1N1 susceptibility.ConclusionsThis is the first study to comprehensively explore the impact of host factors, especially IFN-λ polymorphisms, on H1N1 virus infection. Further elucidation of the underlying mechanisms may help to develop novel prevention and treatment strategies for influenza virus infection.